Readiness of sports infrastructure in supporting of provincial sports events - Ichlasul Amal; Endarman Saputra; Ceppy Pradana Putra (Sriwijaya Journal of Sport, 2025)
Research Problems: Provincial Sports Week Jambi 2026 in Tanjung Jabung Barat requires a well-prepared Sports Centre as the main venue. Research Objectives: This study aimed to determine the state of sports centre facilities and infrastructure in Tanjung Jabung Barat towards the Provincial Sports Week Jambi in 2026. Methods: This study uses a quantitative descriptive approach to assess the facilities, management, and sustainability of the Sport Centre. The sample used was 50 respondents with a sampling technique using Purposive Sampling. The data analysis method uses quantitative and descriptive analysis, using SPSS Version 29. Results: The research shows that the infrastructure indicator received an answer in the "strongly agree" category of 62%, the sports branch facilities and infrastructure indicator received an answer in the "strongly agree" category of 58%, the operational management indicator received an answer in the "strongly agree" category of 54%, and the sustainable aspect indicator received an answer in the "strongly agree" category of 70%. Conclusion: This Management includes routine maintenance but faces coordination and regulatory challenges. Sustainability efforts should involve budget allocation, community use, and private sector collaboration. With improvements, the Sport Centre can serve as an optimal venue for Provincial Sports Week Jambi 2026 and a long-term sports hub.